Gender, Health and Ageing European Perspectives on Life Course, Health Issues and Social Challenges - Backes, Prof. Dr. Gertrud; Lasch, Vera; Reimann, Katja (Alter(n) und Gesellschaft, 2006)
The different research fields - gerontology, gender and health - have generated different views, knowledge and foci on ageing, health and gender. It is now necessary to integrate these aspects into research, policy and practice. The objective of this book is to provide an overview of gender, health and ageing. Important theoretical concepts, such as life course and "Lebenslagen" in old age, or differences in men's health, are introduced. It is increasingly important to build a European basis of knowledge, to conduct discussions on European research findings, and to develop European research frameworks. In this volume, central theoretical debates on gender impacts on life course and old-age health, and vital issues of health research in the context of gender and old age are introduced. Specific aspects, such as the impact of gender and age on cardiovascular health, elder abuse and mental health, or care between gender relations, gender roles and gender constructs, are pointed out. Special attention is given to the impact of social, political and economic change in different New EU Member States, like Hungary, Poland and Slovenia.